Age-related regulation and region-specific distribution of ion channel subunits promoting atrial fibrillation in human left and right atria. Issue 8 (25th May 2019) - Biliczki, Peter; Boon, Reinier A; Girmatsion, Zenawit; Bukowska, Alicia; Ördög, Balázs; Kaess, Bernhard M; Hohnloser, Stefan H; Goette, Andreas; Varró, András; Moritz, Anton; Nattel, Stanley; Ehrlich, Joachim R
Abstract: Aims : Age-induced changes and electrical remodelling are important components of the atrial fibrillation (AF) substrate. To study regional distribution and age-dependent changes in gene expression that may promote AF in human atria. Methods and results : Human left atrial (LA) and right atrial (RA) tissue samples were obtained from donor hearts unsuitable for transplantation and from patients undergoing mitral valve repair. Atrial fibrillation was mimicked in vitro by tachypacing of human atrial tissue slices. Ionic currents were studied by the whole-cell patch-clamp technique; gene expression was analysed by real-time qPCR and immunoblotting. Both healthy RA and RA from older patients showed greater CACNA1c mRNA and CaV1.2 protein expression than LA. No age-dependent changes of Kir2.1 expression in both atria were seen. Remodelling occurred in a qualitatively similar manner in RA and LA. I K1 and Kir2.1 protein expression increased with AF. MiR-1, miR-26a, and miR-26b were down-regulated with AF in both atria. I Ca, L was decreased. CACNA1c and CACNA2b expression decreased and miR-328 increased in RA and LA during AF. Ex vivo tachypacing of human atrial slices replicated these findings. There were age-dependent increases in miR-1 and miR-328, while miR-26a decreased with age in atrial tissues from healthy human donor hearts. Conclusion : Features of electrical remodelling in man occur in a qualitatively similar manner in both human atria. Age-related miR-328 dysregulation and reduced I Ca, L may contribute to increased AF susceptibility with age.